Income Tax Reform under HPP Law: Implications for Tax Justice and Legal Certainty in Indonesia - Dinda Zilfattisa Kusnan (al-Battar: Jurnal Pamungkas Hukum, 2026)
This study aims to analyze juridically the changes in Income Tax provisions introduced by Law Number 7 of 2021 on the Harmonization of Tax Regulations and their implications for the principles of tax justice and legal certainty within Indonesia’s tax system. This research employs a normative legal method using statutory and conceptual approaches, based on primary legal materials in the field of taxation and relevant secondary sources, analyzed qualitatively through deductive reasoning. The findings reveal that the reform of Income Tax under the HPP Law not only modifies the tariff structure and expands the tax base compared to the previous framework under Law Number 36 of 2008, but also reconstructs incentive policies and strengthens tax administration and supervision. Juridically, these changes reflect the state’s effort to establish a more equitable and adaptive income tax system, particularly through progressive rate adjustments and the reinforcement of anti-avoidance rules. Nevertheless, the rapid normative transformation raises challenges concerning legal certainty and consistent implementation. Therefore, this study recommends the development of coherent implementing regulations, sustained public dissemination, and proportional law enforcement to ensure that the objectives of income tax reform are effectively achieved.